KEMAMPUAN LABA BERSIH, ARUS KAS OPERASI, DAN RASIO PIUTANG UNTUK MEMPENGARUHI ARUS KAS MASA MENDATANG PADA PERUSAHAAN FOOD AND BEVERAGE DI BEI - KUSUMA PURBO WANTI, FERRA (: 2303-1719)
Financial reporting can evaluate a company's ability to generate cash and cash equivalents better through the information that is focused on the financial position, statement of changes in financial position and cash flows of the company. This study aims to determine the ability of net income, operating cash flow, and the ratio of receivables effect to future cash flows at a food and beverage company that went public on the Stock Exchange. This type of research is quantitative research that uses explanatory format (described a generalization or explain the relationship of a variable with other variables). The data used are annual financial statements of manufacturing companies that go public in 2007-2010 are included in the category of food and beverage as many as 14 companies. So the number of samples in this study as many as 14 companies. Sources of data taken from www.idx.co.id. Analysis technique used was multiple linear regression analysis. Based on this research, it is obtained that the net income, operating cash flow, receivables and the ratio of significant impact on future cash flows